A study on the relationship between student entrepreneurship intentions using theory of planned behavior of final semester diploma students at UiTM Pahang. / Nurzaihyan Mahmood - Mahmood, Nurzaihyan (Faculty of Business and Management, 2020)
The researcher conducted the study is to identify the A Study on The Relationship Between Student Entrepreneurship Intention Using Theory of Planned Behavior. Theory of planned behavior is the independent variable and Entrepreneurship Intention is dependent variable. There is significant correlation variable in this findings. Attitude toward behavior, Subjective Nonn and Perceived Behavior Control is components of Theory Plan of Behavior. The researcher conducted the study at UiTM, Pahang, Jengka. Questionnaires are distributed to students UiTM in order to collect the data for this finding. The researcher interpret the data received using Statiscal Package for the Social Science (SPSS). The objective of this study is to identify the level of student entrepreneurship intention between Theories of Planned Behavior. The study conducted to observe about relationship of Theory of Planned Behavior with entrepreneurship intention among student UiTM, Pahang. The result obtained was documented in depth through this report. The researcher also come up with several recommendation and suggestion for the future study.